Embracing the reablement approach as a model of restorative care for the elderly - Oyeneyin Babatunde David (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2021)
Objective: To review the efficacy of the reablement approach in management of older persons. Type of study: This is a review study analyzing the evolvement, effectiveness and the spread out of this model of care for old people. Methods: Relevant previous studies on reablement were identified and critically appraised, providing clarity and enhanced understanding of the topic. Customarily, in the management of the elderly over the years, health and social care have always focused on critical and recurrent conditions while little emphasis is placed on strategies for early detection or prevention of old age-related health challenges.  With the world facing the challenge of an aging population with an associated prevalence increase in age-related disabilities, the conception of 'reablement' that promotes independence in older adults by optimizing their intrinsic functional abilities is becoming more popular. An integral part of reablement is the interdisciplinary work that is embedded in it. The Reablement model is an all-inclusive approach as it features preventive, rehabilitative, and health promotion.